Peru’s approach to climate change in the andean mountain region: achieving multidisciplinary regional cooperation for integrated assessment of climate change - Lagos Enríquez, Pablo (2007)
Climate change aggravates the challenges of sustainable development in mountain regions and calls for deeper insights into impacts on the vulnerability of mountain people and their options for adapting to changing conditions. Peru is considered highly vulnerable to climate change. Therefore, its government has initiated a program to strengthen the capacity for transdisciplinary research in order to propose adaptation measures and reduce the negative impacts of climate change. The present article describes the strategy for selecting the study area and for achieving collaboration between natural and social scientists, stakeholders, decision-makers, and other societal groups, in order to carry out an integrated assessment of climate change in the mountainous ecosystems region of central Peru, with an emphasis on vulnerability and adaptation.